2020
DOI: 10.3390/plants9101359
|View full text |Cite
|
Sign up to set email alerts
|

Chia, Quinoa, and Their Coproducts as Potential Antioxidants for the Meat Industry

Abstract: Chia and quinoa have gained popularity among consumers worldwide due to the wide variety of nutrients but also to the bioactive compounds that they contain. Lately, their processing has generated different coproducts (non-commercial grains, flour, partially deoiled flour, rich-fiber fraction, and oil, among others), which could be reincorporated to the food chain with important technological properties, antioxidant activity included. Both sets of ingredients have been revealed a great technological potential f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 112 publications
1
13
0
Order By: Relevance
“…Chia seed is mostly an antioxidant due to the well-known antioxidant properties of PUFAs (rich sources of ALA) and other compounds such as phenolic compounds as well as flavonoids, all of which exert hepatoprotective, antioxidant and anti-inflammatory effects. [40][41][42] In our study, we have shown that chia seed administration increased the serum and liver antioxidant capacity, the GSH content and the SOD, CAT, GPx and GR activities reaching values similar to those of the RD group. In this line, Marineli et al 22 showed a markedly higher plasma and liver antioxidant capacity in chia seed-or chia oil-fed animals for 12 weeks, which seemed to contribute to an improvement in endogenous antioxidant defenses.…”
Section: Papersupporting
confidence: 62%
“…Chia seed is mostly an antioxidant due to the well-known antioxidant properties of PUFAs (rich sources of ALA) and other compounds such as phenolic compounds as well as flavonoids, all of which exert hepatoprotective, antioxidant and anti-inflammatory effects. [40][41][42] In our study, we have shown that chia seed administration increased the serum and liver antioxidant capacity, the GSH content and the SOD, CAT, GPx and GR activities reaching values similar to those of the RD group. In this line, Marineli et al 22 showed a markedly higher plasma and liver antioxidant capacity in chia seed-or chia oil-fed animals for 12 weeks, which seemed to contribute to an improvement in endogenous antioxidant defenses.…”
Section: Papersupporting
confidence: 62%
“…That is why the pandemic will be an excellent opportunity to develop new products in the world of food, using research and development plus innovation strategies. These strategies are aimed at improving the health and wellness of consumers through products enriched with proteins of high biological value (chia, quinoa, amaranth) [1,2], vitamins, minerals, and, above all, dietary fiber, without forgetting that the environment must be respected [3]. In this context, extracts rich in dietary fiber derived from different parts of plants could be used as would-be functional ingredients due to their potential human health benefits that go far beyond supporting bowel regularity [4].…”
Section: Introductionmentioning
confidence: 99%
“…A study assessed the effect of S. hispanica seeds on lipid oxidation and proved that the addition of 0.5-1% chia seeds resulted in a reduction of fat oxidation in the meat product. This was attributed to the presence of numerous polyphenolic compounds, characterized by antioxidant activity, in chia seeds [33,117].…”
Section: Applications Of Chia Seeds In the Food Industrymentioning
confidence: 99%